Preclinical evaluation of a regenerative immiscible bioglue for vesico-vaginal fistula. (15th April 2021) - Kim, Hyo Jeong; Pyun, Jong Hyun; Park, Tae Yoon; Yoon, Sung Goo; Maeng, Seong-Woo; Choi, Hyun Sun; Joo, Kye Il; Kang, Seok Ho; Cha, Hyung Joon
Abstract: Currently, there are no clinically available tissue adhesives that work effectively in the fluid-rich and highly dynamic environments of the human body, such as the urinary system. This is especially relevant to the management of vesico-vaginal fistula, and developing a high-performance tissue adhesive for this purpose could vastly expand urologists' surgical repertoire and dramatically reduce patient discomfort. Herein, we developed a water-immiscible mussel protein-based bioadhesive ( im WIMBA) with significantly improved properties in all clinical respects, allowing it to achieve rapid and strong underwater adhesion with tunable rheological properties. We evaluated in vivo potential of im WIMBA for sealing thermally injured fistula tracts between the bladder and vagina. Importantly, the use of im WIMBA in the presence of prolonged bladder drainage resulted in perfect closure of the vesico-vaginal fistula in operated pigs. Thus, im WIMBA could be successfully used for many surgical applications and improve treatment efficacy when combined with conventional surgical methods. Statement of significance: Vesico-vaginal fistula (VVF) is an abnormal opening between the bladder and the vagina, which is a stigmatized disease in many developing countries. Leakage of urine into internal organs can induce serious complications and delay wound repair. Conventional VVF treatment requires skillful suturing to provide a tension-free and watertight closure. In addition, there is no clinically approved surgical glue that works in wet and highly dynamic environments such as the urinary system. In this work, for potential clinical VVF closure and regeneration, we developed an advanced immiscible mussel protein-based bioglue with fast, strong, wet adhesion and tunable rheological properties. This regenerative immiscible bioglue could be successfully used for sealing fistulas and further diverse surgical applications as an adjuvant for conventional suture methods. Graphical abstract: Image, graphical abstract